Removal of Lead from Liquid Waste Using Liquid Emulsion Membrane - Shama, S.A.; El-Sofany, E.A.; Hasan, M.A.; Atwa, S.T.; El-Taweel, A.A. (Asian Journal of Chemistry, 2015)
Removal of Pb(II) from contaminated aqueous waste using liquid emulsion membrane is of great concern. The liquid membrane is made up of di-2-ethylhexyl phosphoric acid as an extractant, cyclohexane as a diluent, sulfuric acid as a stripper and Span-80 as a surfactant. The extractant and the stripper were selected according to batch extraction experiments. The important parameters affecting the permeation of Pb(II) through the prepared liquid emulsion membrane were investigated. The stability of the prepared membrane which play an important role in the permeation process was studied as a function of surfactant types and concentration.